The Malaysian conference collection: its bibliographic control at the Za'ba Memorial Library, University of Malaya - Zainab, A.N. (Emerald, 1995)
In this article the author describes the management practices adopted by the Za'ba Memorial Library (ZML) for the bibliographic control of Malaysian conference proceedings. The demand for papers presented at conferences (especially in the area of social sciences) is on the increase as more undergraduates and scholars undertake local research. The author also compares the ZML collection with a similar collection at the National Library of Malaysia, noting that both (because of only 20% duplication rate of items between 1980 and 1989) contribute significantly to the bibliographic control of Malaysian conference proceedings.